Measurement properties of tools used to assess suicidality in autistic and general population adults: a systematic review - Cassidy, S.A.; Bradley, L.; Bowen, E.; Wigham, S.; Rodgers, J. (Elsevier, 2018)
Adults diagnosed with autism are at significantly increased risk of suicidal thoughts, suicidal behaviours and dying by suicide. However, it is unclear whether any validated tools are currently available to effectively assess suicidality in autistic adults in research and clinical practice. This is crucial for understanding and preventing premature death by suicide in this vulnerable group. This two stage systematic review therefore aimed to identify tools used to assess suicidality in autistic and general population adults, evaluate these tools for their appropriateness and measurement properties, and make recommendations for appropriate selection of suicidality assessment tools in research and clinical practice. Three databases were searched (PsycInfo, Medline and Web of Knowledge). Four frequently used suicidality assessment tools were identified, and subsequently rated for quality of the evidence in support of their measurement properties using the COSMIN checklist. Despite studies having explored suicidality in autistic adults, none had utilised a validated tool. Overall, there was lack of evidence in support of suicidality risk assessments successfully predicting future suicide attempts. We recommend adaptations to current suicidality assessment tools and priorities for future research, in order to better conceptualise suicidality and its measurement in autism.